(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Childhood malnutrition remains a critical issue in rural India, influenced by various factors including cultural practices. This study explores the cultural influences on child feeding practices among mothers in rural India. Through secondary data analysis, this research aims to identify and understand the cultural beliefs, norms, and practices that impact mothers’ decisions regarding child feeding. The findings will contribute to the development of culturally sensitive interventions to improve child nutrition and health outcomes in rural Indian communities.